Obtenção de parâmetros característicos do meio poroso de reatores de leito gotejante - Frutuoso, Luis Felipe Alves (2018)
Trickle bed reactors are widely used in industry, especially for heterogeneous catalytic systems as in hydroprocessing units (HDR). The optimization of existing units or the design of new reactors is based on data obtained in laboratory scale units. The bed loading procedure has been one of the main concerns between researches due to its influence on data. The main goal of the proposed methodology here is to characterize the bed packing through a constant, which is strongly related to the bed packing condition, obtained from differential pressure data from single phase flow experiments. In this study four packing procedures have been evaluated that have been proposed based on important variants such as vibration, the internal distribution and the dilution material’s particle size. The results have shown that all packing procedures are reproducible and confirmed that all the packing variants evaluated have led to different bed conditions. The differential pressure data was evaluated using Ergun’s equation in the original version and in the adjusted one, which is obtained replacing the first term constant, thus it was seen a substantial improvement in the results using the adjusted model. The four packings have been modeled using CFD. It was found a good agreement between the experimental data with the Brinkman equation. Furthermore, the proposed model has shown sensitivity to describe the packing behavior under different porosity and particle size condition.